Streptococcus Suis Serotype 2 Stimulates Neutrophil Extracellular Traps Formation via Activation of p38 MAPK and ERK1/2 - Ma, Fang; Chang, Xiaojing; Wang, Guangyu; Zhou, Hong; Ma, Zhe; Lin, Huixing; Fan, Hongjie (Frontiers in Immunology, 2018)
Streptococcus suis serotype 2 is a major pathogen of swine streptococcicosis, which result in serious economic loss worldwide. SS2 is an important zoonosis causing meningitis, septicemia and even death in humans. Neutrophil extracellular traps (NETs) constitute a significant bactericidal strategy of innate immune. The battle between SS2 and NETs may account for the pathogenicity of SS2. However, the molecular mechanism underlying release of SS2-induced NETs remains unclear. In this study, SS2 was found to induce NETs within 2-4 h, and was dependent on reactive oxygen species (ROS) from NADPH oxidase. Moreover, SS2 could activate neutrophil p38 MAPK and ERK1/2. Blockage of p38 MAPK or ERK1/2 activation decreased SS2-induced NETs formation by 65% and 85%, respectively. In addition, NADPH oxidase derived ROS inhibition negatively affected phosphorylation of p38 MAPK and ERK1/2 in SS2 induced neutrophils. Both TLR2 and TLR4 were obviously up-regulated by SS2 infection in blood cells in vivo and neutrophils in vitro, which indicates these two receptors are involved in SS2 recognition. Blocking TLR4 signaling could further inhibit the activation of ERK1/2, but not p38 MAPK; however, TLR4 signaling inhibition reduced NETs formation induced by SS2. In conclusion, SS2 could be recognized by TLR2 and/or TLR4, initiating NETs formation signaling pathways in a NADPH oxidase derived ROS dependent manner. ROS will activate p38 MAPK and ERK1/2, which ultimately induces NETs formation.